Buruh Migran Indonesia Dalam Diplomasi Multi-jalur - Anita Afriani Sinulingga; Ranny Emilia (Department of International Relations, Universitas Andalas)
In interacting with other nations within the international level, Indonesia’s traditional diplomacy is conducted by the Ministry of Foreign Affairs. Here, it plays a role as the representative of the government. However, in today’s advanced era, diplomacy is an instrument that should involve every component of the society, including the migrant workers”. The current problematic is that there are hundreds to millions of Indonesian migrant workers residing in other countries but Indonesia has failed to actualize these workers as power for its foreign policy. Every year, hundred of thousands of Indonesians migrate to other countries to work. These workers reside in various countries all over the world, including in ASEAN countries. Malaysia has the second largest number of Indonesian migrant workers after Saudi Arabia. Until today, these Indonesian migrants are merely considered as labor force. They are not valued as structural importance who has bargaining power in diplomatic practice. The purpose of this writing is to operationalize the concept of multi track diplomacy in an attempt to enforce the role of migrant workers as a non-diplomatic group to further strengthen Indonesia’s diplomatic posture. As an agent of the third-track diplomacy, this writing will further describe the role of migrant workers as the foundation of diplomatic strength.